Interlanguage performed by students of English literature study program - Ayudya Whardani; Margana Margana (LingTera, 2019)
The present study attempts to present the evidence of how learners of English as Second Language perform the target language by involving 20 participants from one of state universities in Yogyakarta. The participants are sitting in the first semester majoring English Literature. In investigating the target language performance this study used a writing assignment namely recount text in order to identify language development in relation to grammar acquisition comitted by the learners. Errors made by the learners tend to show interlanguage that the learners performance gains immediate status between native language and target language. The study found that the leaners explored 15 grammar aspects including past tense, modality, to + infinitive , gerund, make, passive voice ,sentence elements, prepositions, articles, collocations, singular and plural nouns, pronouns, relative pronouns, question word order and native language transfer.  The approximate cause of the errors are overgeneralization , learning strategy and native transfer. Moreover, overgeneralization becomes the most frequent in making errors that is by consistently using past tense in dealing with verbs. Thus, it is suggested that the teacher is necessary to sharpen the material spesifically based on actual evidence of learners’ performance in order to accomodate what the learners need.